SWOT Analysis on Kenya Klaten Herbal SMEs - Bartolomeus Galih Visnhu Pradana; Agatha Mayasari (Jurnal Manajemen Sains dan Organisasi, 2023)
Objective - Identifying the internal and external environment through SWOT analysis on Kenya Klaten Herbal SMEs to formulate alternative business development strategies. Design/Methodology/Approach - The research method utilized is descriptive qualitative. Data collection techniques consist of observation, interviews, and life history documentation. Research Findings - The SWOT analysis results indicate that the strengths and opportunities are more dominant compared to weaknesses and threats, thus the policy direction of Kenya Klaten's Herbal SMEs is in a growth strategy condition. Originality/Value - This research plays a role in business development by providing explanations about strategies that the company needs to implement to maximize opportunities and minimize threats.